A Survey on Major Security Issues for Health Data in Wireless Medical Sensor Networks - Gayathri, C; Sathya, D (International Journal of Computer Sciences and Engineering, 2015)
Wireless Sensor Networks (WSN) is an emerging technology that has the potential to transform the way of human life. Healthcare applications are considered a promising field for Wireless Sensor Network, where the patient’s health can be monitored using Medical Sensors. Wireless Medical Sensor Networks (WMSNs) are the key enabling technology in healthcare applications that allows the wearable biosensors to collect the patient’s vital body parameters to be collected by wearable biosensors. Currently WMSN healthcare research focuses on reliable patient communication, mobility of patient and energy-efficient routing. Security and Privacy protection of the collected data are the major issues to be solved in medical sensor networks. This paper deals with various techniques adopted for securing the medical data during the transmission and also deals with the avoidance of unauthorized access.